2022
DOI: 10.24925/turjaf.v10i2.260-262.4662
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Commonly Encountered Parasites in Sheep in Iğdır Province, Turkey

Abstract: Sheep farming is an important segment of the livestock sector in Turkey. However, low meat, milk, leather and wool production due to various parasitic diseases has adversely affected this sector. This study was carried out by using stool and tissue samples collected from 300 sheep registered with the Provincial Directorate of Agriculture and Forestry in Iğdır, Turkey. Stool samples were collected using native, flotation and sedimentation methods to diagnose common parasites. In addition, parasitic diagnoses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Parasitic diseases have an important place in small ruminant farming (Ayaz et al, 2006;Ertaş et al, 2022) It is reported that there is a signi cant morbidity and mortality due to parasitic infections and these diseases in developing or underdeveloped countries in the modern era (Çınar et al, 2018;Ertaş et al, 2022). Moreover, this problem is further complicated by the fact that pets are infected with more than one species at the same time (Ayaz et al, 2006).…”
Section: Introducti̇onmentioning
confidence: 99%
“…Parasitic diseases have an important place in small ruminant farming (Ayaz et al, 2006;Ertaş et al, 2022) It is reported that there is a signi cant morbidity and mortality due to parasitic infections and these diseases in developing or underdeveloped countries in the modern era (Çınar et al, 2018;Ertaş et al, 2022). Moreover, this problem is further complicated by the fact that pets are infected with more than one species at the same time (Ayaz et al, 2006).…”
Section: Introducti̇onmentioning
confidence: 99%
“…The scientific basis for the conservation of biodiversity of various ecosystems is research on the inventory of fauna and parasitic complexes. In natural rangelands, where, as a rule, antiparasitic measures are not carried out, most domestic and wild animals become infected with parasitic diseases and permanently seed the external environment with the invasive principle (Suleimenov et al, 2014;Ertaş et al, 2022). Therefore, the study of the species diversity of parasites and the infection of animals with them is of great interest not only for parasitologists, zoologists, and ecologists but also for veterinary medicine specialists from the point of view of ensuring the parasitological safety of natural ecosystems and developing measures to combat diseases caused by parasites (Roeber et al, 2013).…”
Section: Introductionmentioning
confidence: 99%